Results from the intercalibration of optical low-light calibration sources 2011 - Brändström, B. Urban E.; Enell, Carl-Fredrik; Widell, Ola; Hansson, Thord; Whiter, Daniel; Mäkinen, Sanna; Mikhaylova, Daria; Axelsson, Katarina; Sigernes, Fred; Gulbrandsen, Njål; Schlatter, Nicola M.; Gjendem, Amund Gjerde; et al. (European Geophysical Union, 2012)
Source at https://doi.org/10.5194/gi-1-43-2012 . Following the 38th Annual European Meeting on Atmospheric Studies by Optical Methods in Siuntio in Finland, an intercalibration workshop for optical low light calibration sources was held in Sodankylä, Finland. The main purpose of this workshop was to provide a comparable scale for absolute measurements of aurora and airglow. All sources brought to the intercalibration workshop were compared to the Fritz Peak reference source using the Lindau Calibration Photometer built by Wilhelm Barke and Hans Lauche in 1984. The results were compared to several earlier intercalibration workshops. It was found that most sources were fairly stable over time, with errors in the range of 5–25%. To further validate the results, two sources were also intercalibrated at UNIS, Longyearbyen, Svalbard. Preliminary analysis indicates agreement with the intercalibration in Sodankylä within about 15–25%.